Loop expansion in Yang-Mills thermodynamics - Hofmann, Ralf (Brazilian journal of physics, 2012)
We argue that a self-consistent spatial coarse graining, which involves interacting (anti)calorons of unit topological charge modulus, implies that real-time loop expansions of thermodynamical quantities in the deconfining phase of SU(2) and SU(3) Yang-Mills thermodynamics are, modulo one-particle irreducible resummations, determined by a finite number of connected bubble diagrams.
Gesehen am 16.08.2018